Development and characterization of hydroquinone-loaded nanofiber for topical delivery: effect of chitosan. Issue 3 (3rd April 2019) - Azarbayjani, Anahita Fathi; Talebi, Naimeh; Diba, Kambiz
Abstract: Hydroquinone (HQ) loaded polymer solution was electrospun for its topical application. Nanofibers were then investigated in terms of stability, drug release, and antifungal activity. The effect of chitosan (CS) was investigated on the viscosity, stability, drug release, and antifungal activity of the developed formulation. Results indicate a significantly stable HQ-loaded nanofiber formulation. The addition of CS caused hydration of the drug delivery system and enhanced drug release but reduced its stability. HQ-loaded nanofiber mat showed significant antifungal activity, however, there was no inhibition zone in samples containing CS.